Transfigurations : violence, death and masculinity in American cinema - Grønstad, Asbjørn (Film culture in transition., 2008)
"Transfigurations: Violence, Death and Masculinity in American Cinema suggests a fundamental rethinking of the notion of violence in Hollywood cinema, and discloses the methodological and theoretical inadequacies of a series of common approaches to screen violence. More specifically, the book challenges the traditional understanding of the concept of memesis with regard to film fiction in general and film violence in particular. Transfigurations deconstructs the idea that the film image is a transparent entity, and proposes instead that filmicity is always opaque. In turn, this argument leads to the conclusion that all film fiction is amimetic, and that it entails processes of transfiguration rather representation, aesthetic theorization rather than mimetic reflection. By considering film violence not as a mirror but as a trope, this book shows how the violence in films may be interpreted as a discourse on death and masculinity."--Jacket